Effect of Temperature, Water Activity and Incubation Time on Trichothecene Production by Fusarium cerealis Isolated from Durum Wheat Grains - Erazo, Jessica Gabriela (2023)
Fusarium cerealis is a causal agent of Fusarium Head Blight in wheat, and it produces both deoxynivalenol (DON) and nivalenol (NIV). Nevertheless, the effect of environmental factors on the growth and mycotoxin production of this species has not been studied so far. The objective of this study was to investigate the impact of environmental factors on the growth and mycotoxin production of F. cerealis strains. All strains were able to grow in a wide range of water activity (aW) and temperatures, but their mycotoxin production was influenced by strain and environmental factors. NIV was produced at high aW and temperatures, while optimal conditions for DON production were observed at low aW. Interestingly, some strains were able to simultaneously produce both toxins, which could pose a more significant risk for grain contamination.